2018
DOI: 10.1007/s00204-018-2291-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evidence that benzo[a]pyrene promotes an inflammatory microenvironment that drives the metastatic potential of human mammary cells

Abstract: Benzo[a]pyrene (B(a)P) is a major cancer-causing contaminant present in food such as cooked meats and cereals, and is ubiquitous in the environment in smoke derived from the combustion of organic material. Exposure to B(a)P is epidemiologically linked with the incidence of breast cancer. Although B(a)P is recognized as a complete genotoxic carcinogen, thought to act primarily via CYP-mediated metabolic activation to DNA-damaging species, there is also evidence that B(a)P exposure elicits other biological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Given that the inflammatory response has been reported to modulate GC development [3234] and that BaP is a carcinogen that is most likely ingested during daily human life [35, 36], BaP can induce cancerous lesions in the human stomach and result in gastric carcinogenesis by promoting a pro-inflammatory phenotype [5, 3739]. In addition, feeding of mice with BaP has been an extensively applied method for the establishment of mouse GC models [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the inflammatory response has been reported to modulate GC development [3234] and that BaP is a carcinogen that is most likely ingested during daily human life [35, 36], BaP can induce cancerous lesions in the human stomach and result in gastric carcinogenesis by promoting a pro-inflammatory phenotype [5, 3739]. In addition, feeding of mice with BaP has been an extensively applied method for the establishment of mouse GC models [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Benzo[a]pyrene, a constituent of CS, has been shown to promote inflammation pathways via TNF - α and NF - κB , leading to IL - 6 upregulation, miRNA ( let - 7a , miR - 21 and miR - 29b ) dysregulation and the activation of VEGF [195]. The downregulation of let - 7a and miR - 29b and the upregulation of miR - 21 induced by benzo[a]pyrene in human mammary cells were associated with the altered expression of inflammation mediators.…”
Section: Epigenetics and Inflammationmentioning
confidence: 99%
“…Kamel et al (2012) states that TNF-α is the most widely expressed inflammatory cytokine in breast cancer. Likewise, according to Malik et al (2018) TNFα has been shown to increase breast cancer cell growth. The number of cells expressing TNF-α in mammary carcinoma has been known to be related to tumor grade and plays a role in metastasis in mammary carcinoma.…”
Section: Discussionmentioning
confidence: 99%